A new relationship on transport properties of nanofluids. Evidence with novel magnesium oxide based n-tetradecane nanodispersions - Prado, Jose I.; Vallejo, Javier P.; Lugo, Luis (Powder Technology, 397 (2022) 117082, 2022)
The worldwide increasing of thermal energy consumption fosters new technological solutions based on nanomaterials. The use of nanofluids enhances energy efficiency leading to eco-friendlier devices. Thus, researchers are encouraged to understand how modified thermophysical properties improve heat transfer capability. Magnesium oxide based n-tetradecane nanofluids are designed in terms of stability for cold storage application. Thermal conductivity, viscosity, density, and isobaric heat capacity were determined by transient hot wire, rotational rheometry, mechanical oscillation U-tube, and differential scanning calorimetry. Furthermore, a useful relationship on thermal conductivity and viscosity of nanofluids is proposed based on Andrade, Osida and Mohanty theories. Its reliability is checked with the here reported results and literature data of different nanofluids: titanium oxide within water, silver within poly(ethylene glycol), and aluminium oxide within (1-ethyl-3-methylimidazolium methanesulfonate + water). Similar trends have been found for all nanofluids excepting titanium oxide aqueous nanofluids, this differentiated behaviour being expected by the proposed relationship.